Watson-Crick Linear Grammars - Mohamad Zulkufli, Nurul Liyana; Turaev, Sherzod; Mohd Tamrin, Mohd Izzuddin; Messikh, Azeddin (Springer Singapore, 2019)
In this paper,we define Watson-Crick linear grammars extending Watson-Crick regular grammars Subramanian et al. (CCSEIT’12 proceedings of the second international conference on computer science, science, engineering and information technology 151–156, 2012, [9]) with linear rules, and study their generative power. We show that Watson-Crick linear grammars can generate some context-sensitive languages. Moreover, we establish that the family of Watson-Crick regular languages proper subset of the family of Watson-Crick linear languages but it is not comparable with the family of linear languages.